Designing a Website for the Alumni Association using Software Development Life Cycle - Iqbal, Arif Muhamad; Aldy Rialdy Atmadja (CoreID Journal, 2023)
The rapid development of technology has penetrated into various sectors, including education. Universitas Islam Negeri Sunan Gunung Djati Bandung realizes the importance of participating in technological advances to improve information and communication services. One of the efforts made is to utilize the website to introduce and manage alumni data. This research is focused on the analysis and design of the Informatics Study Program alumni website, with the hope that it can support facilities at the university and provide benefits, especially for alumni of the Informatics Department. The results showed that the development of the Alumni Association website can be done well as a means of facilities for the Alumni Association in informing its work program. In addition, website development is carried out by making front-end with ReactJS and back-end with NodeJS Express on the website can run completed and implemented quite well.